Rhizopus microsporus as Causative Agent of Mucormycosis in COVID-19 Patient - Sedaghatalab, Moslem; Nouripour-Sisakht, Sadegh; Cheraghzadeh, Seyed R; Sabz, Gholamabas; Gharaghani, Maral (Clinical laboratory (Heidelberg), 2022)
The pandemic of coronavirus disease (COVID-19) emerged as a fatal infection, especially in immunocompromised patients. Currently, this infection is managed with systemic corticosteroids. Co-infection of CO-VID-19 with opportunistic fungi is increasingly recognized. We describe a case of rhino-cerebral mucormycosis 12 days following severe COVID-19 in a diabetic patient. He received 50 mg amphotericin B and surgical debridement. The patient's symptoms improved following medical and surgical intervention. Mucormycosis is an uncommon but serious infection that complicates the course of severe COVID-19. Subjects with diabetes mellitus and multiple risk factors may be at a higher risk for developing mucormycosis.